Who Wants to Go Where? Regional Variations in Emigration Intention in Nigeria - Alabi, Tunde; Olajide, Bamidele (African Human Mobility Review, 2023)
There has been an increase in the number of Nigerians desperately leaving the country. In the absence of accurate data on the rate of actual emigration, this study investigated emigration intention in Nigeria, and how it varies between northern and southern Nigeria – two regions with perennial sociocultural differences that have been neglected in migration research. The study also investigated the factors associated with emigration intention. It utilized secondary data from the Afrobarometer survey, including 1,600 Nigerian adults aged 18 and above. Logistic regression models were fitted to address the study objectives. The study found that the emigration intention rate in Nigeria was 35.5%, but it varied from 30.3% in the north to 40.3% in the south. The rate ranged from 26% in the north-east to 46.4% in the south-eastern part of the country. The most preferred destination for northern Nigerians was another country in Africa (32.4%), but it was North America for southerners (43.2%). At the multivariate level, the study found that living in the south, being educated, using the internet frequently, having tolerance for homosexuals, and participating in politics increased the likelihood ofemigration intention. However, being old, employed and having religious tolerance reduced the odds of emigration intention. The regional models revealed notable differences in the influence of age, education, employment, tolerance, and political participation. The study discusses the implications of the findings.